AI-Enabled Green Advertising and Environmental Awareness: A PLS-SEM-Based Evaluation Among Urban Millennials in NCR - Dr. Shefali Khare (European Economic Letters (EEL), 2025)
Aim: The research will focus on the influence of green advertising with the help of AI on the environmental awareness and behavioral intention among the urban young population in National Capital Region (NCR) of India, which consists of millennials. It examines the major advertising dimensions (personalization, interactivity, content relevance, exposure frequency and platform usage) and how they affect the environment awareness. Research Methodology: The method used was quantitative research where a structured questionnaire was issued to the millennials living in the urban areas. The research assessed eight constructs using Likert items of 5-point. The analysis of the data that was extracted concerning 435 valid responses was used to assess the structural relationships between the constructs. Statistical Methods: The measurement and structural models were evaluated through PLS-SEM. Reliability, convergent and discriminant validity were measured by such indicators as Cronbach Alpha, Composite reliability, AVE, Fornell-Larcker Criterion, HTMT ratio, and cross loadings. Path coefficient and t statistics and the corresponding p-values were used through bootstrapping to test hypotheses. Results: The entire aspects of green advertising AI presence appeared to have a positive significant effect on environment awareness. The generalized form also gave credence to the fact that attitude is positively affected by environmental knowledge resulting in a predictable behavioral intention. Each of the hypotheses proposed was substantiated, which implies theoretical validity and model fit. Originality/Value: The present research adds to the body of knowledge through the incorporation of AI technology with green advertising and its relation to environmental behavior in view of the S-O-R framework. It offers for the first time the insights on how the AI tool could be used in sustainable marketing communication to a tech-savvy generation.